Building customer confidence toward internet banking in Kuching branch - Shella Georgina Beatrice, Anak Vernon Nyana (Universiti Malaysia Sarawak (UNIMAS), 2003)
The purpose of this research paper is to examine and investigate customer confidence toward internet banking. It defines the quality factors and other factors for looking at these areas, reviews some recent related literatures and explores areas of overlapping interest.